Factors Behind Deficient Participation of Local Civil Works Contractors in Carrying Out Bituminous Road Works in Tanzania - Makenya, Amon Raphael (International Journal of Sustainable Construction Engineering and Technology, 2021)
Despite the huge investment made by Tanzania government in the road sector development, the participation of local civil works contractors in developing road infrastructure is not satisfactory and is reported to be less by value of the total works undertaken annually in the country. The extent to which local contractors participate in the development of road infrastructure in Tanzania leaves many questions behind, and the factors of their deficient participation are not well established. The objective of this study is to identify the significant factors of deficient participation of local civil works contractors in carrying out bituminous road works in Tanzania and suggest the appropriate means to improve their participation. The methodology used in this study includes critical review of literature, road project reports from Tanroads and discussions with road sector stakeholders. Results from forty four (44) randomly selected bituminous trunk road projects awarded by Tanroads between 2003 and 2012 shows that, only 16 % of all bituminous road projects were awarded to local civil works contractors and the remaining 84% were awarded to foreign contractors. Moreover, participation of local civil works contractors is less by 10% by value of the total works undertaken annually in the country. Further, the study revealed that, inadequate participation of local civil works contractors is predominantly associated with problems such as inadequate capital, low financial capacity, inadequate work opportunities, lack of appropriate construction equipments and plant, lack of skilled personnel and inadequate management skills. However, collective efforts by government and other construction industry stakeholders are needed to increase effective participation of local contractors in the development of road infrastructure in the country. The authors hope that the findings from the current study will increase the stakeholders’ awareness on the participation of local civil works contractors in executing bituminous road works in the country.